Culture, technology, and process in 'media theories': Toward a shift in the understanding of media in organizational research. (September 2019) - Hoof, Florian; Boell, Sebastian K
The concept of 'media' can provide an anchor point for developing organizational theories about information and communication technologies, materiality, communication, and organizational change. However, to date, organizational research often takes the meaning of the term media for granted. This article therefore explores various conceptions of media, outlining how such theories can be used for advancing the conception of media in organizational research. Using three ideal-typical branches of conceptions of media, we explore key concerns regarding media in existing literature outside of organizational research. First, the culture and power branch problematizes how cultural practices and power structures are inscribed through media; second, the technology and infrastructure branch emphasizes the inherent 'eigenlogik' of media technology; and third, the process and change branch explores how existing economic and aesthetic conventions in media persist over time. Using organizational media in general and enterprise social media in particular we discuss how each of these three ideal-typical branches offer pathways for organizational research. Specifically we argue for shifting the use of the term media beyond merely describing tools for communication as media theories offer insights for understanding the long-term consequences of materiality and ontological co-constitution within sociomaterial assemblages.